Antibacterial cotton fibers treated with silver nanoparticles and quaternary ammonium salts. (20th October 2016) - Kang, Chan Kyu; Kim, Sam Soo; Kim, Soojung; Lee, Jintae; Lee, Jin-Hyung; Roh, Changhyun; Lee, Jaewoong
Highlights: Quaternary ammonium salt (QA) and silver nanoparticles (AgNPs) were coated on cotton. The cotton treated with QA/AgNPs showed higher moisture regain than naïve cotton. QA/AgNPs treated cotton revealed synergistic antibacterial properties. Abstract: Cotton fibers were treated chemically with glycidyltrimethylammonium chloride (GTAC), a quaternary ammonium salt, and coated with silver nanoparticles/3-mercaptopropyltrimethoxysilane (3-MPTMS) to increase the antibacterial efficacy. The coating process was accomplished by soaking the cotton fibers into a GTAC solution followed by a dry-cure method, and silver colloid/3-MPTMS solution was then applied at 43 °C for 90 min. The properties of the cotton fibers were analyzed by scanning electron microscopy, X-ray photoelectron spectroscopy (XPS), and thermogravimetric analysis. SEM showed a rough surface when the cotton fibers were treated with GTAC/3-MPTMS/silver nanoparticles due to the increasing surface attachment. The existence of silver and 3-MPTMS on the cotton fibers was confirmed by XPS. The cotton fibers treated with both GTAC and silver nanoparticles showed synergistic antibacterial properties against P. aeruginosa .